Synthesis of three novel curcumin analog compounds and their activity tests against breast cancer based on in vitro, network pharmacology, and molecular docking assessments - Endang Astuti, Jihan Alfiyah Kultsum, Zarah Aulia, Frika Rahmawari, Kasta Gurning,, Sugeng Triono, Winarto Haryadi, Harno Dwi Pranowo (Journal of Applied Pharmaceutical Science, 2025)
Breast cancer, the most common disease suffered by women, causes high mortality compared to other cancer types. This study aims to synthesize mono-carbonyl curcumin analogs and test their cytotoxic activity against four breast cancer cell lines, i.e., MCF-7, T47D, 4T1, and HER2, along with bioinformatics analysis, molecular docking, and pharmacokinetic profile prediction evaluation. Curcumin analogs were produced through aldol condensation, which reacting 3-bromo-4-methoxybenzaldehyde with various ketones to form N-benzyl-4-piperidone (A), 4-piperidone (B), and N-methyl-4-piperidone (C). Pharmacokinetic profiles showed that compounds A–C showed improved absorption, tissue distribution, retention, and toxicity profiles compared to curcumin. However, these compounds did not fully meet the Lipinski criteria, indicating limitations in oral bioavailability. Compound B exhibited the highest anticancer activity against T47D (IC50 = 19.20 μg/ml) and HER2 cells (IC50 = 30.70 μg/ml). Compound A was found to the best against 4T1 cells (IC50 = 174.05 μg/ml) while compound C gave the best activity on MCF-7 cells (IC50 = 110.91 μg/ml). All compounds showed low efficacy, with a selectivity index value of lower than 3. Bioinformatics studies of the network pharmacology approach on cancer pathways showed that mitogen-activated protein kinase 8 protein became the main target of compound A while AKT1 protein was for compounds B and C. Further improvement in their activity and selectivity through targeted delivery systems and further molecular studies are recommended to enhance their therapeutic potential.
Keywords: ADMET, bioinformatics, breast cancer, curcumin analog, molecular docking